M-libraries 5 from devices to people (Facet Publishing, 2015)
Based on the proceedings of the Fifth International M-Libraries Conference held at the Chinese University of Hong Kong in 2014, this work showcases the diversity of innovative and inspiring work that libraries are doing across the world to interact with their users and deliver resources via mobile and handheld devices.